Basil: Philosophical Literacy Meets Biblical Literalism? - Brown, Andrew (Zeitschrift für antikes Christentum, 2022)
Basil of Caesarea’s sermon series On the Hexaemeron occupies a vital place in the early development of the hexaemeral genre. In homily 9 he strongly avows a literal method as he interprets Gen 1, avoiding a figurative method sometimes compared or traced to Origen. Earlier, Basil's dismissive comments might give the impression that he renounced all use of philosophy, natural and metaphysical, in his interpretation of Genesis. Yet parts of his homilies employ current philosophical categories, and he happily employs moral typology in relation to the plants and animals mentioned in Gen 1. These tensions warrant re-examination of the connection between Basil's commitment to a literal interpretation articulated early in homily 9 and his attitude to secular learning. In a sermon series for a general audience, pastoral purposes prevail over intellectual exploration; Basil limits his temptation to indulge in metaphysical speculation. Moreover, Gen 1 itself as a creation narrative seems to Basil to demand realistic and thus a literal treatment. But this literalism does not entail a thoroughgoing rejection of classical philosophy despite his throw-away comments. But he does curtail his philosophical discourse as spiritual benefits diminish and spiritual risks for his listeners increase.